Estimasi Model Substitusi Tidak Sempurna Volume Perdagangan Indonesia - Dwika Darinda; Aprilianto Amir (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2022)
The international trade consists of two components, volume and price. The price component is a deflator for international trade. Meanwhile, the volume component can be regarded as the real condition of international trade. In this paper, the author tries to explain the relationship between export and import volumes according to the theoretical basis. The response variable is the quantity (volume) of imports and exports. Meanwhile, the control variables, such as GDP and REER, are in accordance with the